2021
DOI: 10.1038/s41433-021-01467-4
|View full text |Cite
|
Sign up to set email alerts
|

Virtual clinics for glaucoma care – Patients’ and clinicians’ experiences and perceptions: a qualitative evaluation

Abstract: Background The role of glaucoma virtual clinics has developed to help meet demand for capacity within busy glaucoma services. There is limited research of patient and clinician experiences and perceptions of these clinics and the aim of this study is to provide further information to help improve patient experience and guide service delivery. Methods A mixed methods research design was employed comprising of a patient satisfaction survey, and patient and clinician inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Our study showed high satisfaction rate between the patients who benefit from virtual clinic, similar findings also reported by on local study [19], and multiple international studies [8-13,16-18], primary care-based studies [9][10][11] and specialized care settings studies [9,12,16,18].…”
Section: Comparison With Existing Literaturesupporting
confidence: 90%
See 1 more Smart Citation
“…Our study showed high satisfaction rate between the patients who benefit from virtual clinic, similar findings also reported by on local study [19], and multiple international studies [8-13,16-18], primary care-based studies [9][10][11] and specialized care settings studies [9,12,16,18].…”
Section: Comparison With Existing Literaturesupporting
confidence: 90%
“…Our interviewees did not mention technical issues as compared to some studies that reported technical issues during the consultation. [9,10,15,16]. However, the studies which involved advanced technology has more challenges comparing to basic simple ones.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Both outcomes present the system integration need and cooperation between caregiver and patient. Same dissatisfaction outcome has been obtained in Ophthalmology review from the reason of communication issue with the provided virtual system, even though the main outcome with Glaucoma virtual clinics can be acceptable to both clinicians and patients, including those with a varied complexity of glaucoma and glaucoma related disease [24]. On the other hand; in ENT surgery side aspect, the new system alignments in treatment protocol with virtual care concept should be applied to patients in an out-patient setting [25].…”
Section: ____________________________________________________________...mentioning
confidence: 76%
“…Effective telemedicine services depend on the acceptance and satisfaction of both healthcare users and service providers [ 8 - 10 ]. During the COVID-19 pandemic, a simplified telemedical setup was easy and was widely accepted by diabetic patients and healthcare providers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%